2016
DOI: 10.2105/ajph.2016.303136
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Risk Behaviors and Substance Use Among Men Sexually Victimized by Women

Abstract: A nontrivial fraction of men experience forced sex by women; some of them have elevated sexual risk behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Including male teens in a study on gender discrimination and TDV may obscure the underlying mechanisms; however, recent studies suggest both male and female teens may be victims of TDV. 7,35 Finally, our study was biased toward heterosexual teens and did not assess how other identities and social locations (eg, based on sexuality, gender expression, disability, or immigration status) might factor into experienced multiple oppressions and correlates of TDV.…”
Section: Limitationsmentioning
confidence: 99%
“…Including male teens in a study on gender discrimination and TDV may obscure the underlying mechanisms; however, recent studies suggest both male and female teens may be victims of TDV. 7,35 Finally, our study was biased toward heterosexual teens and did not assess how other identities and social locations (eg, based on sexuality, gender expression, disability, or immigration status) might factor into experienced multiple oppressions and correlates of TDV.…”
Section: Limitationsmentioning
confidence: 99%
“…The majority of the body of literature associates substance use with low-income, marginalised, and disadvantaged groups (Blosnich et al 2011;Pollock et al 2012). The literature also shows that people with intersecting identities, that is combinations or overlap of these group identities, are more likely to be marginalised and discriminated against and show lower levels of mental wellbeing (Carliner et al 2016;Molina et al 2016;Cook et al 2016). Carliner et al (2016) found that while racial discrimination against black Americans contributed to higher rates of illicit drug use, this relationship was even stronger amongst higher socioeconomic sections of this ethnic group.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, alcohol abuse, drug abuse, and increased use of tobacco are commonly reported among male sexual assault victims (Cook et al, 2016;Guina et al, 2016;Isely and Gehrenbeck-Shim, 1997;Peterson et al, 2011;Walker, Archer, and Davies, 2005). Among military veterans who sought care at a VA facility, men and women who had experienced MST had higher odds of substance use disorders than veterans who had not experienced MST (Kimerling et al, 2010;Maguen et al, 2012).…”
Section: Mental Health Carementioning
confidence: 99%